2020
DOI: 10.3390/inorganics8040026
|View full text |Cite
|
Sign up to set email alerts
|

A Partial Anion Disorder in SrVO2H Induced by Biaxial Tensile Strain

Abstract: SrVO2H, obtained by a topochemical reaction of SrVO3 perovskite using CaH2, is an anion-ordered phase with hydride anions exclusively at the apical site. In this study, we conducted a CaH2 reduction of SrVO3 thin films epitaxially grown on KTaO3 (KTO) substrates. When reacted at 530 °C for 12 h, we observed an intermediate phase characterized by a smaller tetragonality of c/a = 0.96 (vs. c/a = 0.93 for SrVO2H), while a longer reaction of 24 h resulted in the known phase of SrVO2H. This fact suggests that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Synthesis of heterostructures and thin films also allows for strain engineering, which may alter anion-site occupation in heteroanionic materials. For instance, experimental and computational studies have revealed that strain can alter preferred lattice positions of different anions in oxynitrides, oxyhydrides, and oxysulfides. However, we are unaware of experimental work demonstrating the use of substrate-induced strain to alter or direct the F incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of heterostructures and thin films also allows for strain engineering, which may alter anion-site occupation in heteroanionic materials. For instance, experimental and computational studies have revealed that strain can alter preferred lattice positions of different anions in oxynitrides, oxyhydrides, and oxysulfides. However, we are unaware of experimental work demonstrating the use of substrate-induced strain to alter or direct the F incorporation.…”
Section: Introductionmentioning
confidence: 99%
“…The substrate employed appears critical for hydride introduction because when a (La 0.3 Sr 0.7 ) (Al 0.65 Ta 0.35 )O 3 (LSAT) substrate is used for x = 0, an oxygen-depleted phase results. 4,28 As can be seen in Figure 4d, the evolution of the cell parameters as a function of x is highly anisotropic, that is, a is nearly unchanged while c increases linearly. It is remarkable that the volume change in the oxyhydride films with x is much steeper than that of the parent Sr 1−x La x VO 3 solid solution (Figure 4h).…”
Section: ■ Results and Discussionmentioning
confidence: 85%
“…The first-principles calculation revealed that the trans -preference caused by the characteristic crystal field splitting as well as a coherent shrinkage along the V–H–V direction due to anion ordering stabilizes the ordered structure . In fact, tensile strain in the thin film sample induces the anion disordering, suggesting that the lattice parameters are strongly connected with the order–disorder phenomena …”
Section: Introductionmentioning
confidence: 99%
“…28 In fact, tensile strain in the thin film sample induces the anion disordering, suggesting that the lattice parameters are strongly connected with the order−disorder phenomena. 29 Herein, we report anion-disordered perovskite Sr 1−x Na x VO 3−y H y (x = 0, 0.05, 0.1, 0.2). High-pressure and high-temperature synthesis from nominal composition SrVO 2 H yielded anion-disordered SrVO 3−y H y (y ∼ 0.4) with a significant amount of byproducts, while Na substitution resulted in an almost pure anion-disordered phase of Sr 1−x Na x VO 3−y H y with an increased amount of hydride anions (y ∼ 0.7 for x = 0.2).…”
Section: Introductionmentioning
confidence: 99%